The gene for the species antigen on human chromosome 11 is on the short arm. - Buck, D; Bodmer, W; Bobrow, M; Francke, U (1976)
A gene (or gene cluster) controlling one (or more) cell surface species antigens has been assigned to chromosome 11. Using hybrids made with cells from a carrier of a balanced reciprocal translocation, 45,XX,t(11;17)(p15;q21), the authors have localized this gene or genes to the short arm of chromosome 11.